Switzerland : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Regulation, Payment Systems, and Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of Switzerland's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Banking Supervision, Securities Regulation, Insurance Regulation, Payment Systems, and Monetary and Financial Policy Transparency. Overall, financial institutions in Switzerland are well capitalized, but the risks of the current environment should not be underestimated. The large internationally active banks have suffered from the recent asset market volatility and the global economic slowdown. The domestically oriented banks are well capitalized, but their lower level of underlying profitability makes them sensitive to the economic cycle.